2023
DOI: 10.1017/jfm.2023.246
|View full text |Cite|
|
Sign up to set email alerts
|

Scaling CO2–brine mixing in permeable media via analogue models

Abstract: Supercritical ${\rm CO}_2$ injection and dissolution into deep brine aquifers allow its sequestration within geological formations. After injection, ${\rm CO}_{2}$ gas phase is buoyancy-driven over the denser aqueous brine, reaching an apparent gravitational stable distribution. However, ${\rm CO}_2$ dissolution in brine propels convection since the mixture is even denser than the underlying brine. This process still needs to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…A similar proportional relationship between finger growth velocity (calculated using the migration distance of the rising fingertip) and characteristic Darcy velocity was also observed in the work of Teng et al 69 The evolution equation of characteristic Darcy velocity can be represented as in eq 14. 23,26 = U gk C…”
Section: Vertical Progression Of Fingersmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar proportional relationship between finger growth velocity (calculated using the migration distance of the rising fingertip) and characteristic Darcy velocity was also observed in the work of Teng et al 69 The evolution equation of characteristic Darcy velocity can be represented as in eq 14. 23,26 = U gk C…”
Section: Vertical Progression Of Fingersmentioning
confidence: 99%
“…The Hele–Shaw cell, a simple apparatus built with a small aperture between two transparent flat plates, has been extensively used to visualize the Darcy flow, including density-driven CO 2 transport. Furthermore, by varying several parameters in the cell, such as aperture, porosity, and vertical or horizontal permeability, it is possible to mimic the transport mechanism similar to that of CO 2 storage in different geological structures. These experimental studies have adopted different visualization techniques to investigate the finger morphology during density-driven CO 2 transport, such as the pH indicator-based method, Schlieren method, particle image velocimetry, laser-induced fluorescence, and interferometry method. ,, Furthermore, several studies have investigated scaling relationships to characterize the convective dissolution rate of CO 2 in brine formations. Mojtaba et al developed a relationship between Sherwood and Rayleigh numbers and CO 2 convective flux at different Rayleigh numbers under 3.45 MPa and 182 < Ra < 20,860. Mahmoodpour et al showed scaling relationships between compensated flux and transition times between successive regimes in the system for experimental fluid with different salt types (NaCl and CaCl 2 ).…”
Section: Introductionmentioning
confidence: 99%